The Shifting Geography of Competitive Advantage:Clusters, Networks and Firms - Jenkins, Mark; Tallman, Stephen (Oxford University Press, 2010)
We consider the dynamics of knowledge-based sources of advantage as they move between geographical locations and multinational and other firm level networks using the specialist context of Formula 1 motor over a fifty nine year period. We suggest that shifts in competitive advantage are underpinned by the movement of both architectural and component knowledge at both the firm and cluster level, and in particular we suggest that isolated firms can both benefit from and add to cluster level knowledge. We conclude by suggesting ways in which MNEs can adapt their approach to both location and knowledge development in order to enhance their ability to create competitive advantage.
An important development in the study of multinational firms and knowledge-based competitive advantage in recent years is the recognition that unique, rent-generating knowledge can be found in many locations around the globe.
Keywords: competitive advantage; Formula 1.; Clusters; knowledge flows; networks